An Epidemiological Survey of Malaria Infection in Espírito Santo State, Brazil, from 2007 to 2017 - Nayna Carvalho Oliveira; Lais Rosa Boscalha; Cinthia Emerich Toledo; Felipe Sarlo Pezzin; Bruno Costanza Cisari; Suellen Rodrigues Maran; Laís Rodrigues Diniz; Pedro Henrique Schultz Corcino Freitas; Adenilton Cruzeiro; Frederico Eutropio; Juliana Rodrigues Tovar Garbin; Marcela Segatto; et al. (Parasitologia, 2023)
Malaria is one of the most important neglected diseases in the world, and Brazil has the largest number of cases on the American continent. In Brazil, this disease is considered to be endemic in the Amazon region, although malaria lethality in extra-Amazonian regions is higher. Recently, it has been shown that malaria cases of autochthonous origin are not uncommon in the southeastern states. Among these states, Espírito Santo (ES) has the highest percentage of reported cases. This study aimed to describe the epidemiological profile and main factors that contribute to the incidence of malaria cases in this region, which corresponded to 4155 notifications in the 2007–2017 period based on data obtained from the Special Center for Epidemiological Surveillance of Espírito Santo. The most affected group was males aged around 40 years old, and most of the cases registered were of autochthonous origin. The number of malaria cases decreased during the period 2007–2017. Among the causative species, P. vivax was predominant, and it was followed by P. falciparum as the second most common species of all malaria cases. The main cities of ES presented high records of malaria disease, with high numbers of malaria cases in Santa Tereza, Domingos Martins, Alfredo Chaves, Santa Leopoldina, and Marechal Floriano. It is up to the local governments to advise the population about the epidemiological situation and to standardize medical care for individuals with suspected malaria.